Comparative study of computed tomography guided fine needle aspiration cytology and trucut biopsy in diagnosis of lung cancer: a report of 81 cases - Sharma, Rishi Kumar; Chhabra, Gaurav; Luhadia, Atul; Sharma, Shubhakaran; Luhadia, S. K. (International Journal of Research in Medical Sciences, 2016)
Background: Lung cancer is the major cause of cancer related deaths all over the world. CT guided FNAC and/or Biopsy of lung mass is an effective modality to diagnose lung cancer, especially in peripherally situated lesions. This study was planned to compare the role of CT guided lung FNAC and Biopsy in diagnosis of Lung cancer. Methods: This is a cross sectional study, done in department of respiratory medicine of a tertiary care teaching hospital of Rajasthan over a period one year. All the patients with suspected mass lesion on chest X-ray and clinical symptoms suggestive of lung cancer were included in the study. CT guided FNAC and biopsy were done in each patient after explaining the risks. Results: CT guided procedures were done in 81 patients of suspected lung cancer. CT guided FNAC yielded positive results in 75 patients while it was negative in 6 patients. CT guided lung biopsy was positive in all patients. Squamous cell carcinoma was most common type encountered malignancy. Conclusions: CT guided lung FNAC and Biopsy is a simple and safe method with high diagnostic accuracy for diagnosis of Lung cancer.